2017
DOI: 10.1002/2017jb014052
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Stability of Plate‐Like Behavior Caused by Hydrous Mantle Convection and Water Absorption in the Deep Mantle

Abstract: We investigate the cycling of water (regassing, dehydration, and degassing) in mantle convection simulations as a function of the strength of the oceanic lithosphere and its influence on the evolution of mantle water content. We also consider pseudo‐plastic yielding with a friction coefficient for simulating brittle behavior of the plates and the water‐weakening effect of mantle materials. This model can generate long‐term plate‐like behavior as a consequence of the water‐weakening effect of mantle minerals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 60 publications
1
27
1
Order By: Relevance
“…From the high values at the surface we see a rapid drop off in the water content caused by the major reduction of C w , max of basaltic material at 80 km depth. This continues down to 150 km where we find the choke point in the ambient mantle saturation table (as described in Nakagawa & Iwamori, ), after which, the rate at which the average water content decreases (radially) reduces as it approaches 300 km (the point where basaltic material's water carrying capacity drops off significantly). We then find that from 330 km down to the upper‐lower mantle boundary at 660 km, the average mantle water content increases due to the large storage capacity of ambient mantle material colder than 1500 K (up to 15 wt%).…”
Section: Resultssupporting
confidence: 63%
“…From the high values at the surface we see a rapid drop off in the water content caused by the major reduction of C w , max of basaltic material at 80 km depth. This continues down to 150 km where we find the choke point in the ambient mantle saturation table (as described in Nakagawa & Iwamori, ), after which, the rate at which the average water content decreases (radially) reduces as it approaches 300 km (the point where basaltic material's water carrying capacity drops off significantly). We then find that from 330 km down to the upper‐lower mantle boundary at 660 km, the average mantle water content increases due to the large storage capacity of ambient mantle material colder than 1500 K (up to 15 wt%).…”
Section: Resultssupporting
confidence: 63%
“…However, our previous studies have indicated that the evolution of the mantle water mass cannot be determined with a simple regassing-degassing balance, which essentially incorporates the excess water transport associated with the dehydration reaction (Nakagawa et al 2015;Nakagawa and Spiegelman 2017;Nakagawa and Iwamori 2017). Hence, the water solubility limit of each mantle mineral should be included to compute the excess water in the dehydration reaction.…”
Section: Introductionmentioning
confidence: 99%
“…By considering this effect, our previous studies have indicated that the mantle water evolution may be strongly regulated by the water solubility limits of upper mantle minerals. In addition, the rheological properties of hydrous mantle rocks may affect the behavior of surface plate motion, with hydrous mantle conditions allowing for more vigorous surface plate motion and a much larger friction coefficient than dry mantle conditions (Nakagawa and Iwamori 2017). Such vigorous surface plate motion induced by a pseudo-plastic rheology may transport large amounts of water (i.e., several ocean masses) into the deep mantle over geologic timescales (approximately 2 billion years), and the mantle transition zone can absorb this amount of water over geologic timescales (Nakagawa and Iwamori 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the volatile content of the surface environment, particularly the presence of liquid water is thought to have a large feedback on the interior, for example by favoring plate tectonics (e.g. Nakagawa and Iwamori, 2017 i) Atmospheric escape that covers interaction between radiation by the sun and the upper atmosphere, leading to the loss of volatile into space (Tian, 2015). It is generally most efficient early in the evolution of the planet.…”
Section: Degassing Volatile Cycles and Continental Cyclingmentioning
confidence: 99%